Poder local, espaços para a cidadania: um estudo de caso - Vizzotto, Assis Roque (2004)
This work makes a study about the local power, and its relationship with the process of construction of the citizenship, whose actual effectiveness happens only when the citizen has full access to the basic essential services. Participation and access to education, healthiness, habitation, safeness, and work, are indispensable conditions to the whole development to the human being. In this sense, this work shows a study about political emancipations occurred in Faxinal do Soturno-RS with before and after socioeconomic emancipation. The results show a major offer of basic services to the so much citizen in the city as in the interior, promoting the welfare and the fundamental freedom of the citizen to choose his government. This nearness allows a major transparency in the complex political relationships. So it s necessary to decentralize the politic power in order to develop the citizenship in a better way.